Passapu: Makna dan Identitas Laki-Laki Suku Kajang - Mrs. Isfawani; St. Junaeda; Dimas Ario Sumilih (Rayhan Intermedia, 2022)
This study aims to find out about Passapu as the identity of Kajang Tribe men and the meaning of using Passapu for Kajang Tribe men. This study uses qualitative data. The informants were selected through the Kajang Tribe traditional holders, Kajang Tribe men who use passapu in their daily life and the Kajang Tribe community who know about passapu. Data was collected by means of observation, interviews and documentation. The results of the study show: 1) Passapu is the identity of the completeness of the traditional clothing of the Kajang Tribe. The traditional clothing of the Kajang Tribe for men is a shirt in the form of a black shirt, black or white shorts, black sarong and a passapu or headband. The hallmark of the clothing worn by men of the Kajang tribe lies in the headgear (passapu). Self-identity that people who can use passapu are Kajang tribe men who have grown up and know their spouses. 2) The meaning of using passapu for men from the Kajang tribe has a symbol of honesty and maturity. The symbol of honesty and maturity has the meaning of how we are able to control our thoughts to do good or evil in accordance with the life guidelines of the pairs of ri kajang. It has meaning in each element in the passapu, and has several functions, namely practical functions, aesthetic functions, and symbolic and philosophical functions.